Single friction plate clutch design for cars with power of 77 kW and speed of 6000 rpm using finite element method - Darmawan, Agung Setyo; Syarif, Junaidi; Purboputro, Pramuko Ilmu; Yulianto, Agus; Hamid, Abdul; Noviyanto, Noviyanto (Applied Research and Smart Technology (ARSTech), 2020)
A single friction plate clutch is one part of the components in a vehicle that is used to transmit power and rotation from the driveshaft to the driven shaft without slippage. This study aims to compare the results of mathematical calculations with analysis based on finite element methods in the design of a single friction plate clutch such as shaft, spline, friction plate, and spring. The analysis was carried out on the shaft made of S30C, spline made of S30C, friction plates made of steel alloy, and springs made of carbon steel. The component was drawn by Solidworks-17 software and analysed by Abaqus 6.14-5 software based on finite element methods. The study was performed by comparing the sizes of the various elements. A comparison of simulation processes using the stress concept of von-misses was conducted. The results of mathematical calculations with the simulation process were compared, and the maximum deviation was 2.881%. The deviation was considered acceptable. Based on von-misses’ maximum stress, the material was safe to use due to below the yield strength.